The Raffia-swamps as sources or sinks of avifauna: a first approach to the problem. - Beneyto, Davinia (2013)
In the Tortuguero region, northeastern Costa Rica, tropical forests are home to over 300 species of birds. Within this ecosystem, wetlands dominated by the raffia palm Raphia taedigera and the royal palm Manicaria saccifera extend in large monospecific swamps locally known as yolillales. These wetlands are characterized by low plant diversity, simple structure, waterlogged soils, and extended hydroperiod. There is hardly any information on the bird communities that inhabit or uses yolillales. We describe this ornitofauna, comparing the species that inhabit the palm-swams and in the adjacent forest in terms of species richness and diversity. During October-November 2008, we used transects and hearing stations in both habitats in four locations in the region. We located a total of 11 bird species in the palm-swamps and 31 in the adjacent forests. Our observations suggest that palm-swamps have lower species richness than adjacent forests and that these environments also differ in species composition. Despite their low diversity, yolillales are employed by species with different degrees of vulnerability, so that they may be important for bird conservation in the region. Sampling in yolillales is very hard, so our data should be considered preliminary. Further efforts in these environments are needed to improve our knowledge on the bird community that uses them.